Current Evidence on Traditional Chinese Exercises for Quality of Life in Patients With Essential Hypertension: A Systematic Review and Meta-Analysis - Song, Yang; Li, Jialin; István, Bíró; Xuan, Rongrong; Wei, Sheng; Zhong, Guanghui; Gu, Yaodong (Frontiers in Cardiovascular Medicine, 2021)
Essential hypertension is one of the most common chronic diseases seen in primary human health care that could lead to various health problems and reduce the quality of life (QOL). This study was performed to evaluate the effects of traditional Chinese exercises (TCE) on QOL in patients with essential hypertension. Three English databases and one Chinese database were searched for randomized controlled trials (RCTs) until August 2020. A total of 13 RCTs with 1361 hypertension patients met the inclusion criteria, 10 trials employed Tai Chi, 3 trials employed Qigong, including Dongeui Qinggong, Yijinjing, and Wuqinxi. Despite a large heterogeneity within studies, it is demonstrated that TCE may be an effective therapy to improve the QOL of hypertension patients. More specific, compared with no intervention, the meta-analysis presented that Tai Chi significantly improved both the physical and mental component of 36-item short-form health survey (SF-36) QOL scale, and it was found that simplified 24-form Tai Chi with the frequency of 30 to 50 min per time at 5 to 8 sessions per week was the most common used setting. The pooling also revealed that Tai chi and Qigong had some significantly positive effects on QOL based on other scales. However, more rigorously designed RCTs are warranted for further verification. This systematic review and meta-analysis of RCTs demonstrated that Tai chi may be an effective therapy to improve the QOL of patients with essential hypertension. All these findings provide helpful information for hypertension patients and medical personnel.